2018
DOI: 10.1111/jcmm.13625
|View full text |Cite
|
Sign up to set email alerts
|

TP53INP1 inhibits hypoxia‐induced vasculogenic mimicry formation via the ROS/snail signalling axis in breast cancer

Abstract: Tumour protein p53‐inducible nuclear protein 1 (TP53INP1) is a tumour suppressor associated with malignant tumour metastasis. Vasculogenic mimicry (VM) is a new tumour vascular supply pattern that significantly influences tumour metastasis and contributes to a poor prognosis. However, the molecular mechanism of the relationship between TP53INP1 and breast cancer VM formation is unknown. Here, we explored the underlying mechanism by which TP53INP1 regulates VM formation in vitro and in vivo. High TP53INP1 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 45 publications
(103 reference statements)
2
18
0
Order By: Relevance
“…Moreover, to further verify HIF1α involvement in VM, we mimicked hypoxia using cobalt chloride and observed a strong increase in vessel-like structure formation which was totally blocked by HIF1α siRNA as well as in the presence of the pharmacological HIF1 inhibitor acriflavine. Altogether our data on TNBC agree with other studies in different tumor types (57,59) and interestingly provide the first evidence that TLR3 stimulation induces HIF1αmediated VM in a very aggressive breast cancer cell line.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, to further verify HIF1α involvement in VM, we mimicked hypoxia using cobalt chloride and observed a strong increase in vessel-like structure formation which was totally blocked by HIF1α siRNA as well as in the presence of the pharmacological HIF1 inhibitor acriflavine. Altogether our data on TNBC agree with other studies in different tumor types (57,59) and interestingly provide the first evidence that TLR3 stimulation induces HIF1αmediated VM in a very aggressive breast cancer cell line.…”
Section: Discussionsupporting
confidence: 91%
“…Many studies reported that VM is related to hypoxia-activated signaling pathways and metastatic phenotype (50,55). It has been demonstrated that the overexpression of HIF1α protein is associated with VM in human gallbladder cell lines (56) as well as in breast cancer (57). TNBC is a subtype which is aggressive, metastasizes and has a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the EMT regulators Twist1, Slug and Snail were found to play a role in EMT and VM in hepatocellular carcinoma and breast cancer (19,24,27). Therefore, this study examined Twist1, Slug and Snail expression in PSCs and PSCCs (Fig.…”
Section: Twist1 Expression Indicates a Poor Survival Of Patients Withmentioning
confidence: 97%
“…These transcription factors can bind to the E-cadherin promoter to regulate transcriptional activity, and the decreased levels of E-cadherin result in decreased cell adhesion and increased cell invasion and metastasis [22,30]. EMT involves a large number of signaling pathways, such as the transforming growth factor-beta (TGF-β) signaling pathway [13,47], Wnt signaling pathway [48,49] and Notch signaling pathway [31,32,50,51]. Furthermore, there are two miRNA regulatory networks that are considered prominent regulators of EMT: the miR34-SNAIL1 and miR200-ZEB1 axes that regulate EMT epigenetically [47].…”
Section: Epithelial-mesenchymal Transition and Vmmentioning
confidence: 99%
“…Research has shown that snai1 and slug regulate the process of EMT by repressing E-cadherin transcription to disrupt cell-tocell adhesion. Furthermore, reactive oxygen species; (ROS) can activate Snai1 to promote cancer progression [48]. It has been demonstrated that slug expression was significantly associated with the CSCs phenotype and VM formation in HCC [49].…”
Section: Epithelial-mesenchymal Transition and Vmmentioning
confidence: 99%